Conversion-space time profiles of stirred tank reactors continuously fed with reactants and catalyst under conditions of strong catalyst deactivation - Flaschel, E.; Margot, A.; Dohmen, M.; Renken, A. (Chemical engineering science, 1995)
Feeding continuously operated stirred tank rectors with reactants and homogeneous catalysts subject to inactivation will usually lead to a limited substrate conversion with increasing space time. However, it is shown that a maximum of conversion may be observed under certain circumstances. Guided by experimental evidence, the theoretical background is discussed for identifying reaction systems for which such conversion maxima at distinct space times may be obtained. The analysis shows that this phenomenon may only be observed if the catalyst undergoes deactivation characterized by a kinetics of less than first order. Therefore, a likely case for experimental verification consists in an enzymic reaction accompanied by proteolytic degradation of the substrate transforming enzyme due to the presence of a protease.